Adsorption of radioactive cesium using synthesized chitosan-g-poly(acrylic acid/N-vinylcaprolactam) by γ-irradiation. (July 2023) - Emara, Amr M.; Elsharma, Emad M.; Abdelmonem, Islam M.
Abstract: To remove radioactive cesium ions from wastewater, graft copolymer of chitosan- g -poly(acrylic acid/N-vinylcaprolactam) [CTS-P(AA/VC)] was synthesized. The shape, thermal stability, and structure of the graft copolymer were all successfully characterized by SEM, TGA, and FT-IR. Batch sorption experiments were carried out in order to evaluate the effects of various parameters such as pH, contact time, adsorbate initial concentration, and temperature. The kinetics data of batch interaction were also extensively covered with various (linear and non-linear) models of sorption kinetic such as pseudo-first-order, pseudo-second-order, and intra-particle diffusion models. Langmuir and Freundrich equations isotherm models were studied by linear and non-linear equations. To determine the best-fitting equations, the correlation coefficient (R 2 ) and the normalized standard deviation Δq (%) were used as error analysis methods. It appeared briefly that the linear and non-linear forms of pseudo-second order and the Langmuir model are better fitted for kinetic and isotherm models, respectively. The elimination capability for cesium-134 radionuclides was ∼115 mg g -1 . Thermodynamic parameters showed exothermic, spontaneous nature and decreased randomness during the adsorption process. After the adsorption studies, the elution process was successfully proceeds by using different eluting agents. The findings suggested that CTS-P(AA/VC) graft copolymer could be a useful material for treating cesium-134 ions-containing liquids. Highlights: Chitosan-g-poly(acrylic acid/N-vinylcaprolactam) was synthesized by gamma irradiation grafting copolymerization technique. Gamma-irradiation renders a higher grafting efficiency of the graft copolymer. High adsorption capacity of the graft copolymer towards cesium-134 radionuclide was shown. Different studies of linear and nonlinear forms for both kinetic and isotherm models were investigated. Elution process was studied by using different eluting agents.